Network, Cryptography, and the Next World to Come: An Everlasting American Techno-millenarianism? - Pucheu, David (Zygon, 2024)
To understand the nexus between networked cryptography and American religiosity, it is essential to embed this inquiry within the broader context of religious imaginaries associated with communication networks in nineteenth-century North America and their evolution into the spiritual landscape of the twentieth century. Throughout United States history, network imaginaries have exerted a substantial influence, engaging in a continuous dialogue with the evolution of religious thought, attributing eschatological expectations to networks, and ascribing them with a profound sense of ultimate purpose and significance. This investigation finds its ultimate context within the early techno-libertarian communities of 1990s California, pivotal in shaping the design, development, and objectives of networked cryptography online, ultimately giving birth to cryptocurrencies and the blockchain protocol.